2008
DOI: 10.1097/ccm.0b013e318170a375
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hospital mortality in a population-based cohort of patients with acute lung injury*

Abstract: The predictors of mortality in patients with acute lung injury are similar to those predictive of mortality in the general intensive care unit population, indicating disease heterogeneity within this cohort. Accordingly, APACHE III predicts mortality in acute lung injury as well as a model using variables selected specifically for patients with acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 46 publications
(54 reference statements)
3
97
1
2
Order By: Relevance
“…Several studies previously identified these variables as independently associated with death. 15,17,18 What, then, does this study 12 add to the literature? Villar and colleagues deviate from most, but not all, 16 prior studies by developing and validating an extremely simple prediction tool that retains excellent performance.…”
Section: See the Original Study On Page 420mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies previously identified these variables as independently associated with death. 15,17,18 What, then, does this study 12 add to the literature? Villar and colleagues deviate from most, but not all, 16 prior studies by developing and validating an extremely simple prediction tool that retains excellent performance.…”
Section: See the Original Study On Page 420mentioning
confidence: 99%
“…In fact, at least a dozen prior studies aimed to fully characterize the predictors of mortality among patients with acute lung injury (ALI) or ARDS or to integrate predictors of death into a prognostic index specific to this disease. [13][14][15][16] Villar et al are also not the first to identify age, airway plateau pressure, and oxygenation as predictors of mortality in ARDS. Several studies previously identified these variables as independently associated with death.…”
Section: See the Original Study On Page 420mentioning
confidence: 99%
See 1 more Smart Citation
“…They also proposed a score combining arterial pH (protective per 0.1 more alkalotic), minute ventilation (protective when <9 L/min), PaCO 2 (protective per 5 mmHg increase), and PaO 2 /FiO 2 (associated with mortality when decreasing) (2). The overall in-hospital mortality in their study was 38.5% and the predictive value of the score was better than the acute physiology and chronic health evaluation (APACHE) III in their development cohort, although not different in their validation cohort (2). Later, the same group validated a simpler clinical predictive score (3).…”
Section: Introductionmentioning
confidence: 97%
“…In ARDS, a lot of studies have reported many predictors of prognosis (2)(3)(4)(5)(6). Very recently, Villar et al proposed a new score called the "APPS" which is very simply based on age, PaO 2 /FiO 2 and plateau pressure (Pplat) (7).…”
Section: Introductionmentioning
confidence: 99%